Paleobiological Perspectives on the Early Upper Paleolithic Human Transition in the Northwestern Old World - Erik Trinkaus (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The emerging consensus that the emergence of modern humans in the northwestern Old World involved temporally and geographically varying degrees of admixture between Neandertals and early modern humans within the early Upper Paleolithic provides the framework for assessing the complex mosaic of biobehavioral changes which took place across the transition. Despite a series of paleobiological similarities involving cognitive, masticatory and locomotor behaviors, as well as temporal and cultural overlap between the two groups, there remain contrasts in the anterior dentition, the upper limb, femoral structural patterns, stress levels, demographic profiles and stable isotopes. These changes reflect principally the improvements in technology and subsistence of the earlier Upper Paleolithic. Moreover, there are indications that the biobehavioral shift started within the initial Upper Paleolithic Neandertals.